Normas sociais e expressões do racismo em crianças - Silva, Khalil da Costa (2014)
This study has as its objective to determine the impact of antiracism social norm about the expression of children‟s racial attitudes. Although, Racism is convicted in democratic societies, it has been verified in studies conducted in the context of intergroup relations. Researches conducted with adults have indicate that, in line with the anti-racism norm, individuals inhibit expression of Racism at the explicit level, however there is evidence that prejudice and racial discrimination persist, being expressed in indirect and subtle ways. 72 White children (43 boys and 29 girls) participated in this research, which were distributed among three different groups according to age: 6-7years, 8-10 years and 11-12 years. Attitudes of these children towards the White and Black groups and normative parameters that they verify in adults, friends and in themselves to interact with these groups were observed. Racial attitudes were analyzed by three measures: a scale of racial attitudes-MRA, a measure of social distance and an experimental procedure in which the impact of the anti-racism norm on the child´s behavior was manipulated by conditions of presence / absence of a Black interviewer. Contingency analysis indicated that all three groups studied here recognize the presence of antiracism norm, however they react differently to the presence of this norm. An analysis of variance between age of children and the scores obtained on the scale MRA revealed that children between 6 and 7 years old show elevated levels of explicit prejudice in comparison with the other groups. In contrast, children over 8 years of age have low levels of explicit prejudice and more significant levels of anti-racism attitude. Planned comparisons, however, indicated the presence of subtle racism. Although the children didn‟t evaluate the outgroup (Black) in a negative way, children remain evaluating the ingroup (White) positively. The data obtained from the measurement of social distance indicated, after a contingency analysis, greater sensitivity to anti-racism norm in older children. Between 6 and 7 years of age, children manifest rejection of Black, between 8 and 10 years old they just reject the Black in situations which involve higher degree of intimacy. After 10 years, however, there is expression of favoritism to Black. Regarding the experimental procedure, analysis of variance revealed no significant effect of the manipulation of the social norm, but there were effects of interaction between the child´s age and the target of choice (White / Black). This analysis indicated higher levels of racial discrimination against Blacks between children aged 6 to 10 years old and inhibition of racism among participants over the age of 10. Results confirm the theoretical considerations about new forms of expression of racism and the socio-cognitive development and show that the inhibition of explicit forms of racial prejudice and discrimination observed in adults, begins to emerge in childhood average.